Monitoring the Sheet Metal Defect of Stamping Process - Chuan Huat, Ng; Chai, Zhi Ping (Research Progress in Mechanical and Manufacturing Engineering, 2020)
In automotive manufacturing industry, among all the forming process the hot press forming was one of the most vital forming processes. The sheet metal forming process was very common in manufacturing industry for producing parts for lightweight vehicles. However, catastrophic failure resulted in high losses to the industry occurred due to late detection of defects. This had become an issue in the manufacturing industry. Therefore, in order to solve the problem, non-destructive test was employed in manufacturing process. At first the case study was made in this project regarding the hot press forming process, the material used in stamping process, and the common type of failure that occurred in sheet metal stamping. Next, the case study moved onto different types of ultrasonic monitoring system for monitoring the condition of metal. There were four case studies regarding the ultrasonic monitoring system in this thesis and each case study consisted of one ultrasonic monitoring system. The four ultrasonic monitoring systems were categorized into contact ultrasonic monitoring system and non-contact ultrasonic monitoring system. All the methods in each case study reviewed had different method in generating and receiving ultrasonic wave. Among the four case studies one of the presented results was in graph form while another 3 was in the form of image. The methods reviewed as well as the results from each method were compared. At the last part of this project, the ultrasonic monitoring method that possess the most advantages in hot press forming process was chosen. The supportive explanation is given in order to strengthen the chosen method.